Unprecedented inhibition of P-gp activity by a novel rutheniumcyclopentadienyl compound bearing a bipyridine-biotin ligand - Côrte-Real, Leonor (Eur J Med Chem, 2018)
Two new ruthenium complexes, [Ru(η(5)-Cp)(PPh(3))(2,2’-bipy-4,4’-R)](+) with R = CH(2)OH (Ru1) or dibiotin ester (Ru2) were synthesized and fully characterized. Both compounds were tested against two types of breast cancer cells (MCF7 and MDA-MB231), showing better cytotoxicity than cisplatin in the same experimental conditions. Since multidrug resistance (MDR) is one of the main problems in cancer chemotherapy, we have assessed the potential of these compounds to overcome resistance to treatments. Ru2 showed exceptional selectivity as P-gp inhibitor, while Ru1 is possibly a substrate. In vivo studies in zebrafish showed that Ru2 is well tolerated up to 1.17 mg/L, presenting a LC(50) of 5.73 mg/L at 5 days post fertilization.